RIGHT TO BAIL OR NOT TO BAIL: A SOCIO LEGAL ANALYSIS* (International Journal of Food and Nutritional Sciences, 2021)
The term ‘bail’ originated from an old French verb ‘bailer’ which means ‘to give’ or ‘to deliver’. Bail refers to the provisional release of the accused in a criminal case in which the court is yet to announce the judgment. The term ‘bail’ means the security that is deposited in order to secure the release of the accused. The earliest examples of bail date to the late 13th century, when sheriffs had the right to either hold a criminal or let the criminal go. Eventually, this would evolve into a formal system – by 1275, there were certain crimes that could receive bail and certain crimes that could not.